Meningkatkan Kompetensi Sumber Daya Manusia Untuk Masa Yang Mendatang - Sela Septiana; Riyanto Nur Wicaksono; Afifah Widiya Saputri; Nizar Azmi Fawwazillah; Mochammad Isa Anshori (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Human resources are the most dominant factor in an organization that is built based on needs and implementation. Effective human resource (HR) management must be considered in order to increase competitiveness in the global market and contribute to creating competence in an organization. At this time, human resource management (HR) in the future will become a major concern in the world of business and management, which is a key factor in preparing society to face challenges in the future which are increasingly complex and dynamic, so that organizational planning, implementation and control of resources is needed. human resources in the organization to achieve goals effectively and efficiently. With this, in a business world that continues to develop, it is important for organizations to understand and develop competencies so they can face the challenges and obstacles that continue to arise. Then, a future filled with technological changes, market dynamics and global challenges requires human resources (HR) who have relevant and competent skills and knowledge who are able to compete to maintain and increase the competitiveness of an organization. Success or failure depends on the ability of human resources to carry out their duties and functions. This does not only apply to workers, but in educational institutions, and in society for the future stages of their lives. Formal and informal education, lifelong learning, and access to information technology are key elements in ensuring continued competency. Apart from that, organizations and governments need to play an active role in creating an environment that supports the growth of human resource (HR) competencies. By increasing human resource competency, society can be better prepared to face future technological, economic and socio-cultural changes. The aim of this research is to provide competency development in organizations so that they are able to produce superior human resources (HR) in facing the future involving skills that are relevant to market needs. The research method used in this research is the literature study method. Where researchers study and analyze then provide appropriate descriptions in the form of competencies, organization and methods. The results obtained show that the development of appropriate organizational competencies can provide benefits such as better adaptation to changes in the innovation environment and more effectiveness, as well as achieving organizational competency excellence which requires understanding their business context and identifying the most relevant basic competency components so that they are effective in achieving goals. their strategy.